School nutrition and activity : impacts on well-being - Hassan, Areej (Apple Academic Press, 2015)
Childhood obesity is a major public health crisis nationally and internationally. This insightful compendium provides valuable information and assesses the research foundations behind several school initiatives to help combat the epidemic of obesity in children and adolescents, particularly using interventions to increase physical activity. The book looks at the issue from three levels: first, the effects of unhealthy eating and lack of exercise on a number of health outcomes in children and adolescents; second, successful small- and large-scale school-based interventions; and finally, synthesis of current literature and translation into specific guidelines and recommendations.